International Legal Cooperation in The Field of Food Security and Agriculture - KHODJAYEVA, AZIZA BAHTIYAROVNA (The journal of contemporary issues in business and government, 2021)
In this article you will learn about global food security, the fight against hunger and human rights to food, as well as international cooperation between Uzbekistan and the FAO, the UN specialized agency for food quality in society in the fight against poverty.